Adducing crystalline features from Raman scattering studies of cubic SiC using different excitation wavelengths. (16th February 2017) - Chen, Shuai; Wan, Lingyu; Xie, Deng; Qiu, Zhi Ren; Jiang, Xiaodong; Tin, Chin-Che; Feng, Zhe Chuan
Abstract: A series of cubic 3C–SiC/Si samples with different thicknesses grown by chemical vapor deposition (CVD) was studied by Raman spectroscopy using laser excitation with different wavelengths plus spectral line shape analysis via two theoretical methods. Through comparative UV and visible excitation Raman measurements and theoretical analysis, the TO intensity was mainly affected by laser penetration depth and crystalline quality. The difference spectra were utilized to remove the second-order Raman signal from Si substrate. Using theoretical Raman simulation on LO-phonon and plasmon-coupling (LOPC) mode, the top layer near to the surface has big difference in electrical and optical properties compared to the deeper layer.